PENGARUH PENERAPAN APLIKASI MOBILE PAJAK (M-PAJAK) TERHADAP KESADARAN WAJIB PAJAK UNTUK MEMBAYAR PPH FINAL PADA UMKM DI KECAMATAN WATES KABUPATEN KEDIRI - Duwi Riningsih; Andy Chandra; Krissantina Eferyn (Jurnal Bina Akuntansi, 2023)
This research was conducted in the MSME Group, Wates District, Kediri Regency. This MSME group has members who are included in the MSME category who pay Final Income Tax according to PP scheme No. 23 of 2018. The Mobile Tax application provides various features to facilitate the taxation activities of MSME actors. The purpose of this study is to find out whether the use of Mobile Tax has an influence on taxpayer awareness in paying Final Income Tax. The method used to analyze the data is SPSS version 26 and the method of analysis is simple linear regression analysis. The results of this study are that the application of the Mobile Tax Application has a significant influence on taxpayer awareness to pay final income tax for SMEs, Wates District, Kediri Regency. Keywords: Mobile Pajak, Final Income Tax, MSME